Redesigning and validating the tricot farmer feedback process - 1000FARMS Platform (2025)
This poster summarizes the redesign and validation of the tricot farmer feedback process, an initiative led by the Alliance of Bioversity and CIAT under the 1000FARMS platform. The effort addresses the inconsistent use of feedback forms among tricot trial participants, which limits the participatory nature of the approach. By combining participatory design and in-field testing, the team co-developed a streamlined feedback sheet and diploma used across five Nigerian states. The new process was tested with 44 farmers and assessed using observations, interviews, and comprehension checks. Findings show that 72% of farmers found the form highly useful, with many reporting increased trust and a sense of recognition. The poster also highlights plans to improve usability through localized language versions, clearer iconography, and ClimMob integration for offline and automated feedback delivery